Sensory processing sensitivity is negatively associated with sensation seeking - Reidulf G. Watten; Frode Volden; Hilde Visnes Trå (Current Issues in Personality Psychology)
Background This study investigated the relationship between sensory processing sensitivity and sensation seeking.